Biology inquiry mapping effects on students' concept understanding and visual literacy - Paz, Arby D. (College of Education, University of the Philippines Diliman, 2018)
This study is an investigation of the effects of Biology Inquiry Mapping on students concept understanding and visual literacy. It involved 110 eight graders at a national high school in Caloocan during the fourth quarter of Academic Year 20162017. The experimental group was composed of 60 students and was exposed to the Biology Inquiry Mapping Teaching Approach (IMTA) while the conventional group was composed of 50 students and was taught using the Conventional Teaching Approach (CTA). The research instruments used were Biology Concept Understanding Test (BCUT) and Visual Literacy Test (VLT). Two-tailed t-test for independent samples was used to determine the comparability of the two groups prior to the treatment. One-tailed t-test for independent samples was done on the mean posttest scores in the BCUT and VLT to determine if there was a significant difference between the two groups after the treatment. One-tailed paired samples t test was used to compare the mean pretest and posttest scores in BCUT and VLT to determine if each group improved significantly after the treatment. One tailed t-test for related samples was used to compare the mean pretest and posttest scores of the IMTA group for each item of VLT. Furthermore, simple linear regression was used to determine if the students' Visual Literacy has a positive effect on Concept Understanding. All hypotheses were tested at .05 level of significance. It was found that Inquiry Mapping Teaching Approach significantly improved students' biology concept understanding and certain components of the visual literacy skills. Visual literacy is a significant positive predictor of concept understanding.